AB1242 COLCHICINE USE DURING PREGNANCY: CASE REPORTS. (June 2019) - Duman, Nesrin Caglayan; Karabacak, Murat; Idriz Oglu, Medine Gulcebi; Inanc, Nevsun; Turgan Asik, Zehra Nur; Atagündüz, Pamir; Ozkula, Songul; Gulhan, Rezzan; Goren, Zafer; Onat, Filiz; Direskeneli, Haner; Karaalp, Atila
Abstract : Background: If used during pregnancy it is known that colchicine passes through the placenta to the fetus 1 . Although it has been shown to increase the risk of congenital malformations in animal studies, there is no increase in undesirable results in humans 2 . The guidelines indicate that the use of colchicine in pregnancy and lactation is appropriate 3, 4 . However, data from clinical studies and case reports for the use of colchicine during pregnancy are not sufficient. Objectives: The aim of this study was to evaluate pregnant and/or nursing patients who were consulted to our teratology information center for colchicine use. Methods: Colchicine treated patients during pregnancy was included in this study. Patients consulted to our information service between 2012- 2018 were evaluated for risk assessment of colchicine. Information regarding pregnancy outomes was recorded by telephone interviews with patients. Results: Indications for colchicine use in 34 cases (33 patients; one of them had pregnancy twice) were familial Mediterranean fever (n=21), Behcet's disease (n=9), systemic lupus erythematosus (n=1), ankylosing spondylitis (n=1) and vasculitis (n=1). Of the cases, 22 used the drug in pregnancy and lactation, 12 used only in pregnancy period. Of the 34 pregnancies, three had elective termination of pregnancy (the reason in one case was cytomegalovirus infection, the other is unplanned-unwanted and the other was unknown) and three had spontaneous abortion.Twenty eight had given birth, 19 of them were term and 9 of them were preterm. Delivery mode of 18 were caesarean and 10 of them were vaginal birth. A total of 30 live birth infant (two twins) exposed to colchicine due to their mother's treatment. Twenty three infant was healthy and the remaining 7 had different problems. Four of them cardiac [minor cardiac septal defect which not needs operation (n=2), pink tetralogy of fallot (n=1), heart valve stenosis (n=1)], nephrolithiasis, inguinal hernia and death (respiratory distress after birth) (table 1 ). Conclusion: Currently, systematic review and meta-analysis driven data suggests that colchicine does not significantly increase the incidence of foetal malformations or miscarriage and colchicine for FMF should not be withheld on this basis during pregnancy. Although the causality between colchicine use and the above reported mostly cardiac and rare problems such as tetralogy of fallot is not proven, the contribution of colchicine cannot be ruled out totally and should be beard in mind in cases of colchicine use for indications other than FMF or Behçet's disease. References: [1] Indraratna PL, et al. Use of colchicine in pregnancy: a systematic review and meta-analysis. Rheumatology (Oxford). 2018 Feb 1;57(2):382-387. [2] reprotox.org [3] Götestam Skorpen C, et al. The EULAR points to consider for use of antirheumatic drugs before pregnancy, and during pregnancy and lactation. Ann Rheum Dis. 2016 May;75(5):795-810. [4] .Breastfeeding and Maternal Medication. World Health Organization, Geneva, Switzerland, 1995 Disclosure of Interests: None declared